2020
DOI: 10.1080/02656736.2020.1747646
|View full text |Cite
|
Sign up to set email alerts
|

Identifying predictive factors for efficacy in high intensity focused ultrasound (HIFU) ablation of benign thyroid nodules – a retrospective analysis

Abstract: Objective: Since it is unclear whether clinical parameters can independently predict the subsequent treatment response following high intensity focused ultrasound (HIFU) ablation of benign thyroid nodules, we aimed to examine clinical factors that may independently predict 12-month efficacy after HIFU treatment. Methods: One hundred and forty patients who had single ablation were categorized into two groups, those with 12-month nodule shrinkage above the median (Group I, n ¼ 70) and with shrinkage below or equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Logistic regression analysis showed that age (≤45 years) was an important risk factor for PTC, in line with the findings of Yu et al. 21 Microcalcification is caused by the deposition of calcium salts at the tip of the nipple or the secretion of calcium salts by the tumor itself, and has been considered to be the most specific sign of PTC. In this study, the incidence of microcalcification was higher in PTC patients compared with the control group, and logistic regression identified it as an independent risk sign for thyroid PTC.…”
Section: Discussionsupporting
confidence: 85%
“…Logistic regression analysis showed that age (≤45 years) was an important risk factor for PTC, in line with the findings of Yu et al. 21 Microcalcification is caused by the deposition of calcium salts at the tip of the nipple or the secretion of calcium salts by the tumor itself, and has been considered to be the most specific sign of PTC. In this study, the incidence of microcalcification was higher in PTC patients compared with the control group, and logistic regression identified it as an independent risk sign for thyroid PTC.…”
Section: Discussionsupporting
confidence: 85%
“…Minimally invasive therapy is mainly divided into chemical ablation and thermal ablation. Thermal ablation refers to radiofrequency ablation (RFA), microwave ablation (MWA), laser ablation (LA) and high-intensity focused ultrasound (HIFU) 4 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these thermal ablation techniques, RFA is the most widely applied. 9,10 RFA of thyroid diseases, first reported in 2001, [11][12][13] is considered efficacious and safe for treatment of BTNs. 14,15 To date, no lifethreatening complications related to RFA have been reported.…”
Section: Introductionmentioning
confidence: 99%